Raman spectroscopic study of the mineral qingheiite Na2(Mn2+,Mg,Fe2+)2(Al,Fe3+)(PO4)3, a pegmatite phosphate mineral from Santa Ana pegmatite, Argentina. - Frost, Ray Leslie (2014)
The pegmatite mineral qingheiite Na2(Mn2+,Mg,Fe2+)2(Al,Fe3+)(PO4)3 has been studied by a combination of SEM and EMP, Raman and infrared spectroscopy. The studied sample was collected from the Santa Ana pegmatite, Argentina. The mineral occurs as a primary mineral in lithium bearing pegmatite, in association with beausite and lithiophilite. The Raman spectrum is characterized by a very sharp intense Raman band at 980 cm^-1 assigned to the PO4^3- symmetric stretching mode. Multiple Raman bands are observed in the PO4^3- antisymmetric stretching region, providing evidence for the existence of more than one phosphate unit in the structure of qingheiite and evidence for the reduction in symmetry of the phosphate units. This concept is affirmed by the number of bands in the m4 and m2 bending regions. No intensity was observed in the OH stretching region in the Raman spectrum but significant intensity is found in the infrared spectrum. Infrared bands are observed at 2917, 3195, 3414 and 3498 cm^-1 are assigned to water stretching vibrations. It is suggested that some water is coordinating the metal cations in the structure of qingheiite.